PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN TATA KELOLA SEBAGAI VARIABEL MODERASI - Josephine, Kezia; Oktavia, Christine; Lestari, Amanda (Accounting Global Journal, 2026)
This study aims to analyze the effect of environmental performance on firm value and examine the role of corporate governance as a moderating variable. Corporate governance in this study is proxied by managerial ownership and the audit committee. The research method used is quantitative with panel data regression analysis. The study sample consisted of 19 companies listed in the LQ45 index on the Indonesia Stock Exchange during the 2021–2024 period, with a total of 76 observations selected using a purposive sampling technique. The results show that environmental performance has a significant effect on firm value. Furthermore, managerial ownership has been shown to moderate the relationship between environmental performance and firm value, while the audit committee has no effect. The limitations of this study lie in the limited sample size of LQ45 companies and the relatively short research period. Therefore, further research is recommended to expand the sample and include other variables such as sustainability performance, corporate risk, intellectual capital, and macroeconomic conditions to provide a more comprehensive understanding of the factors influencing firm value. Keywords: Firm Value, Environmental Performance, Corporate Governance, Managerial Ownership, Audit Committee.